Influence of Tempo and Rhythmic Unit in Musical Emotion Regulation - Fernández-Sotos, Alicia; Fernández-Caballero, Antonio; Latorre, José M. (Frontiers in Computational Neuroscience, 2016)
This article is based on the assumption of musical power to change the listener’s mood. The paper studies the outcome of two experiments on the regulation of emotional states in a series of participants who listen to different auditions. The present research focuses on note value, an important musical cue related to rhythm. The influence of two concepts linked to note value is analyzed separately and discussed together. The two musical cues under investigation are tempo and rhythmic unit. The participants are asked to label music fragments by using opposite meaningful words belonging to four semantic scales, namely “Tension” (ranging from Relaxing to Stressing), “Expressiveness” (Expressionless to Expressive), “Amusement” (Boring to Amusing) and “Attractiveness” (Pleasant to Unpleasant). The participants also have to indicate how much they feel certain basic emotions while listening to each music excerpt. The rated emotions are “Happiness”, “Surprise”, and “Sadness”. This study makes it possible to draw some interesting conclusions about the associations between note value and emotions.